Exhausted Minds, Passionate Hearts: The Silent Struggle of Academic Burnout - Hamzah, Fatimah Bibi; Abdul Manan, Dewi Izzwi; Mohtaram, Saifuddin; Abdullah, Nik Mazlinahaiza; Abdul Aziz, Mohd Azril (Journal of Applied Science, Engineering, Technology, and Education, 2025)
Burnout, characterized by chronic physical, emotional, and mental exhaustion, has become an increasingly recognized issue in academia, particularly within higher education institutions where teaching, research, and administrative responsibilities often overlap. This study investigates the prevalence, causes, and impact of burnout among 729 academic staff members at Kolej Poly-Tech Mara (KPTM) Sdn. Bhd. Utilizing the Maslach Burnout Inventory (MBI) along with additional data on workload, institutional support, and individual coping strategies, the research provides an in-depth analysis of burnout within the institution. The findings identify excessive workload, administrative burdens, and inadequate support systems as the primary drivers of burnout. Additionally, the study highlights the adverse effects of burnout on both personal well-being and professional effectiveness, with many staff reporting moderate to high levels of emotional exhaustion and depersonalization. Based on these insights, the study proposes solutions such as more equitable workload distribution, enhanced wellness programs, and the establishment of a more supportive work environment. By implementing these strategies, KPTM can alleviate burnout, improve staff well-being, and enhance overall institutional performance.